Suitability of alternatives to rectal temperature measurements in pet rodents, rabbits and ferrets - Stans, Jelle (Slovenian veterinary research, 2023)
Body temperature is a vital parameter to assess the health of exotic animals. Rectal thermometry is a common way to measure body temperature in rodents, rabbits and ferrets and often considered the gold standard. However, taking a rectal temperature often involves restraint and can lead to stress in these animals. To avoid the stress of rectal temperature measurements, alternative (often less invasive) techniques have been utilized in several species. These methods include tympanic thermometry, axillary thermometry and infrared thermography. It is however important to establish whether these strategies yield comparable readings to the gold standard. Therefore, a literature review was performed using the MedLine and Google Scholar databases. Base terms referring to rectal temperature and thermometry were combined with species-specific search terms. Relatively few studies were identified about alternatives to rectal temperature measurements in rodents, rabbits and ferrets. In general, it can be noted that only transponder measurements have repeatedly been described to be a valid alternative to rectal temperature measurement. Further research should be conducted.
Keywords: alternative; alternatives; beli dihurji; Body Temperature; Ferrets; glodavci; kunci; Rabbits; rectal temperature; rektalna temperature; Rodentia; rodents